Non-Small Cell Lung Adenocarcinoma Problem-Based Learning Case: Monia P. Neu - Heimo Riedel; Mohammed Almubarak (Association of American Medical Colleges, 2015)
Abstract Problem-based learning (PBL) is a common instructional format used at many medical schools. It promotes active, self-directed learning, connecting medical students to their future real-world experience as well as enhancing training and problem-solving skills, teamwork, and interdisciplinary interactions. The PBL small-group format provides a unique opportunity over both semesters for first-year medical students to study clinical cases in a self-directed fashion and develop professional skills at various levels. The advantages of the presented lung cancer case are numerous. Clinical presentation is typically late since symptoms are not obvious and initial diagnosis is frequently misleading. A considerable number of tests are required to arrive at the final diagnosis, providing a variety of learning opportunities, as do the initially successful treatment options, including an example of personalized medicine. The follow-up and typical relapse provide additional learning opportunities, including the inevitable failure of therapy and the psychosocial issues surrounding end-of-life care. This case was implemented in the spring semester in February 2014 over three 90-minute sessions. One hundred twelve first-year medical students divided into groups of eight took the course. The lead author served as a facilitator for one of the 14 groups and received direct feedback about all aspects of the case from the students' perspective. In addition, feedback was received from other facilitators in informal discussions. Finally, the case was evaluated by each group of students on a standard form after it had been concluded. The critique received was overall very favorable and helped optimize the case for this resource. Most points were minor, but comments led to rebalancing of the material between sessions to aim at a similar amount of new material introduced between Sessions 1 and 2. Since students have formal opportunities to research learning issues only after Sessions 1 and 2, the new material introduced in Session 3 is kept to a minimum. It is planned to continue to update the case based on future student feedback and new developments.